ChemInform Abstract: K2CO3‐Mediated, Direct C—H Bond Selenation and Thiolation of 1, 3, 4‐Oxadiazoles in the Absence of Metal Catalyst: An Eco‐Friendly Approach. Issue 14 (April 2015) - Rafique, Jamal; Saba, Sumbal; Rosario, Alisson R.; Zeni, Gilson; Braga, Antonio L.
Abstract: An efficient, economical, and green K2 CO3 ‐promoted procedure for the synthesis of selenated and thiolated oxadiazoles through C—H bond functionalization in the absence of metal catalyst is developed.